Enhancing E-Marketing Competence of Islamic Boarding School Students: A Case Study of Al Muin Syarif Hidayatullah - Firman Yudianto; Teguh Herlambang; Mukhtar Adinugroho; Mohamad Yusak Anshori; Ima Kurniastuti; Rachma Rizqina (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to explore the effectiveness of e-marketing training in increasing the sales revenue of coffee products in Al Muin Syarif Hidayatullah Islamic Boarding School. Using qualitative research methods, the study collected and analyzed data from interviews with students and school officials, as well as observations of the e-marketing implementation in the coffee production business. The results show that e-marketing can significantly increase the sales revenue of the boarding school's coffee products. The study concludes that e-marketing training is necessary to optimize the utilization of the internet and social media platforms for promotional purposes. The implication of this study is that e-marketing competence can be enhanced among Islamic boarding school students, contributing to the promotion of their institutions and improving their skills and knowledge of digital media. This study highlights the importance of using social media platforms for marketing purposes in Indonesia and the potential impact of e-marketing on increasing sales revenue. Highlights: E-marketing training effectively increased the sales revenue of the boarding school's coffee products, demonstrating the potential of digital promotion strategies. The integration of e-marketing education within the Islamic boarding school curriculum contributed to enhancing students' digital skills and knowledge, preparing them for a technology-driven future. The study shows a positive social impact by promoting the boarding school through e-marketing efforts, fostering better community awareness and engagement with the institution's initiatives. Keywords: E-marketing training, Sales revenue, Coffee products, Islamic Boarding School, Digital media skills.